2019
DOI: 10.3892/ijmm.2019.4247
|View full text |Cite
|
Sign up to set email alerts
|

Pistacia weinmannifolia ameliorates cigarette smoke and lipopolysaccharide‑induced pulmonary inflammation by inhibiting interleukin‑8 production and NF‑κB activation

Abstract: Pistacia weinmannifolia (PW) has been used in traditional Chinese medicine to treat headaches, dysentery, enteritis and influenza. However, PW has not been known for treating respiratory inflammatory diseases, including chronic obstructive pulmonary disease (COPD). The present in vitro analysis confirmed that PW root extract (PWRE) exerts anti-inflammatory effects in phorbol myristate acetate- or tumor necrosis factor α (TNF-α)-stimulated human lung epithelial NCI-H292 cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 59 publications
1
24
0
1
Order By: Relevance
“…Pistacia weinmannifolia (PW) is used as a herbal medicine in China (16,17) and its major metabolites possess biological activities, such as inhibitory activities against histamine release (16,18,19). In a previous study, it was confirmed that the anti-inflammatory activities of P. weinmannifolia root extract (PWRE) in PMA/tumour necrosis factor-α-stimulated airway epithelial cells and in pulmonary inflammatory response induced by cigarette smoke and lipopolysaccharide (LPS) (20). Based on these results and those of other studies (16-20), which reflect the anti-inflammatory activities of PWRE on pulmonary inflammation, it was hypothesized that PWRE could exert a protective effect against ovalbumin (OVA)-induced lung inflammation.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Pistacia weinmannifolia (PW) is used as a herbal medicine in China (16,17) and its major metabolites possess biological activities, such as inhibitory activities against histamine release (16,18,19). In a previous study, it was confirmed that the anti-inflammatory activities of P. weinmannifolia root extract (PWRE) in PMA/tumour necrosis factor-α-stimulated airway epithelial cells and in pulmonary inflammatory response induced by cigarette smoke and lipopolysaccharide (LPS) (20). Based on these results and those of other studies (16-20), which reflect the anti-inflammatory activities of PWRE on pulmonary inflammation, it was hypothesized that PWRE could exert a protective effect against ovalbumin (OVA)-induced lung inflammation.…”
Section: Introductionmentioning
confidence: 81%
“…In a previous study, it was confirmed that the anti-inflammatory activities of P. weinmannifolia root extract (PWRE) in PMA/tumour necrosis factor-α-stimulated airway epithelial cells and in pulmonary inflammatory response induced by cigarette smoke and lipopolysaccharide (LPS) (20). Based on these results and those of other studies (16-20), which reflect the anti-inflammatory activities of PWRE on pulmonary inflammation, it was hypothesized that PWRE could exert a protective effect against ovalbumin (OVA)-induced lung inflammation. Therefore, the aim of the present study was to evaluate the regulatory effects of PWRE against eosinophil recruitment and Th2 cytokines, IgE and mucus overproduction, which are the major characteristics of allergic asthma.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Traditional Chinese medicine (TCM) has been demonstrated to exert a pivotal role in the treatment of infectious diseases. For instance, Pistacia weinmannifolia J. Poisson ex Franch has been reported to effectively suppress the pulmonary inflammation stimulated by cigarette smoke (CS) and lipopolysaccharide (LPS) [ 7 ]. Schisandra sphenanthera Rehd.…”
Section: Introductionmentioning
confidence: 99%